Time–frequency analysis of railway bridge response in forced vibration. (August 2016) - Cantero, Daniel; Ülker-Kaustell, Mahir; Karoumi, Raid
Abstract: This paper suggests the use of the Continuous Wavelet Transform in combination with the Modified Littlewood–Paley basis to analyse bridge responses exited by traversing trains. The analysis provides an energy distribution map in the time–frequency domain that offers a better resolution compared to previous published studies. This is demonstrated with recorded responses of the Skidträsk Bridge, a 36 m long composite bridge located in Sweden. It is shown to be particularly useful to understand the evolution of the energy content during a vehicle crossing event. With this information it is possible to distinguish the effect of several of the governing factors involved in the dynamic response including vehicle's speed and axle configuration as well as non-linear behaviour of the structure. Highlights: Enhanced time–frequency analysis of railway bridge signals. Use of Continuous Wavelet Transform with Modified Littlewood–Paley basis. Offers clearer results than any previous analysis on bridge signals. Allows for the identification of the main factors affecting bridge response. Suggested approach applied on real measured signals.